2014
DOI: 10.1111/jir.12167
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of healthcare use, ill health and mortality in adults with intellectual disabilities and mealtime support needs

Abstract: Background Adults with intellectual disabilities (ID) experience a wide range of eating, drinking and/or swallowing (EDS) problems, for which they receive diverse mealtime support interventions. Previous research has estimated that dysphagia (difficulty swallowing) affects 8% of all adults with ID and that 15% require some form of mealtime support. People with ID (whether they require mealtime support or not) also experience a greater burden of ill health and die younger than their peers in the general populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…107 Neither found an increase in consultation among their adults with ID when the authors compared their study results with expected consultation levels estimated using national data. 108 Our study has the advantage of directly comparing consultation behaviour within practices, accounting for any practice variations or trends.…”
Section: Consultationsmentioning
confidence: 99%
“…107 Neither found an increase in consultation among their adults with ID when the authors compared their study results with expected consultation levels estimated using national data. 108 Our study has the advantage of directly comparing consultation behaviour within practices, accounting for any practice variations or trends.…”
Section: Consultationsmentioning
confidence: 99%
“…5 Although published research to date has focused on people with a wide range of severity for ID, restrictions by small samples, short follow-up periods and limited sample representativeness existed. [19][20][21][22][23] Specifically, an elevated risk of mortality from bronchopneumonia of around 6.5-fold was reported in a cohort with moderate to severe ID in the UK, 21 and respiratory infection was found the most common cause of death over a 1-year period in a UK cohort of adults with ID receiving mealtime support for any eating, drinking or swallowing problem. 20 In a Taiwanese institutional sample of people with ID followed for up to 4 years, pneumonia was the topmost reason for hospitalisation.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22][23] Specifically, an elevated risk of mortality from bronchopneumonia of around 6.5-fold was reported in a cohort with moderate to severe ID in the UK, 21 and respiratory infection was found the most common cause of death over a 1-year period in a UK cohort of adults with ID receiving mealtime support for any eating, drinking or swallowing problem. 20 In a Taiwanese institutional sample of people with ID followed for up to 4 years, pneumonia was the topmost reason for hospitalisation. 19 Another study in Canada reported a more than twofold adjusted relative risk of asthma admission of people with ID, identified by population-based medical and educational databases, comparing to people without ID.…”
Section: Introductionmentioning
confidence: 99%
“…This is potentially concerning, particularly as only 30% (91/306) of eligible patients consented. However, low consent rates are not unusual for research in ID: in Perez et al [26]–a study looking at adverse outcomes in adults with ID and mealtime support—only 142 consent to take part out of an identified population of 726, a rate of 20%. It is difficult to recruit from the ID population for many reasons, such as the capacity to consent and, relatedly, the frequent need to include family and carers in the research.…”
Section: Discussionmentioning
confidence: 99%